2008
DOI: 10.1007/s00018-008-8295-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural biology of the purine biosynthetic pathway

Abstract: Purine biosynthesis requires ten enzymatic transformations to generate inosine monophosphate. PurF, PurD, PurL, PurM, PurC, and PurB are common to all pathways, while PurN or PurT, PurK/PurE-I or PurE-II, PurH or PurP, and PurJ or PurO catalyze the same steps in different organisms. X-ray crystal structures are available for all 15 purine biosynthetic enzymes, including seven ATP-dependent enzymes, two amidotransferases and two tetrahydrofolate-dependent enzymes. Here we summarize the structures of the purine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(198 citation statements)
references
References 89 publications
4
194
0
Order By: Relevance
“…In addition, we measured the interaction of DndE B7A-N110 with PAPS, ATP or ADP using the isothermal titration calorimetry assay (Supplementary information, Figure S3). In contrast with the early prediction [10][11]13], DndE B7A-N110 showed no binding affinities to any of them (Supplementary information, Figure S3), consistent with the fact that the DndE B7A-N110 structure includes neither a 5′-PSB motif nor a 3′-PB motif for PAPS and PAP binding [14], nor a glycine-rich P loop for ATP or ADP phosphate binding as seen in the NCAIR synthetase [15,16]. Taken together, the crystal structure of DndE B7A-N110 reveals that DndE is neither a sulfotransferase nor a NCAIR synthase analogue, but a possible nicked ds-DNA binding protein with a previously unrecognized fold.…”
Section: Dear Editorsupporting
confidence: 65%
“…In addition, we measured the interaction of DndE B7A-N110 with PAPS, ATP or ADP using the isothermal titration calorimetry assay (Supplementary information, Figure S3). In contrast with the early prediction [10][11]13], DndE B7A-N110 showed no binding affinities to any of them (Supplementary information, Figure S3), consistent with the fact that the DndE B7A-N110 structure includes neither a 5′-PSB motif nor a 3′-PB motif for PAPS and PAP binding [14], nor a glycine-rich P loop for ATP or ADP phosphate binding as seen in the NCAIR synthetase [15,16]. Taken together, the crystal structure of DndE B7A-N110 reveals that DndE is neither a sulfotransferase nor a NCAIR synthase analogue, but a possible nicked ds-DNA binding protein with a previously unrecognized fold.…”
Section: Dear Editorsupporting
confidence: 65%
“…Purine biosynthesis is highly conserved in the Bacteria and Archaea in terms of the penultimate step in the pathway responsible for ribonucleate formylation 45 . All bacteria sequenced so far use the PurH1 enzyme for this step, whereas the majority of Archaea use the PurP enzyme.…”
Section: Functional Diversity and Novel Findingsmentioning
confidence: 99%
“…The structural data showed that human phosphoribosylpyrophosphate amidotransferase (hPPAT) and human adenylosuccinate lyase (hASL) are tetrameric, human trifunctional glycinamide ribonucleotide transformylase (hTrifGART) and human bifunctional aminoimidazole carboxamide ribonucleotide transformylase/inosine monophosphate cyclohydrolase (hATIC) are dimeric, human bifunctional carboxyaminoimidazole ribonucleotide synthase/succinylaminoimidazole carboxamide ribonucleotide synthetase (hPAICS) is octameric, and only human formylglycinamidine ribonucleotide synthase (hFGAMS) is monomeric (12). It follows that, in vivo, PPIs should also be observed for individual proteins as they oligomerize.…”
Section: Adapting the Tango Assay For Purinosomementioning
confidence: 99%
“…These proteins showed the highest frequencies of clustering and co-localization in purinosome images (2). Based on its structure and the co-localization data, hFGAMS was proposed to provide a scaffold for purinosome formation (12). In the initial experiments (Fig.…”
Section: Adapting the Tango Assay For Purinosomementioning
confidence: 99%